Economic burden and treatment patterns for patients with diffuse large B-cell lymphoma and follicular lymphoma in the USA. (11th March 2019) - Ren, Jinma; Asche, Carl V; Shou, Yaping; Galaznik, Aaron
Aim: Diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) are common types of non-Hodgkin's lymphoma, and real-world evidence continues to be lacking for healthcare costs and utilization among DLBCL and FL patients. Our study aims to describe medical and pharmacy costs and health resource utilization and to characterize longitudinal treatment patterns among these patients.Methods: A retrospective observational study was performed among adult patients with DLBCL or FL using the US MarketScan (Truven) administrative claims data from 1 January 2007 to 31 December 2015. Diagnoses of DLBCL and FL were based upon ICD-9 codes. Identifications of treatment lines involved 30 lymphoma-specific anticancer systemic agents. Direct healthcare costs and utilizations were computed in the 1-year postdiagnosis period. Generalized linear models with a gamma link were used to compare healthcare costs between therapies with and without rituximab.Results: A total of 2767 DLBCL and 5989 FL patients received frontline therapy. The majority received treatment within 3 months after initial diagnosis (DLBCL 79.9% and FL 62.4%) and were treated with rituximab or bendamustine either alone or in combination (DLBCL 67.4% and FL 84.7%). The total healthcare costs were US 15, 555 and 10, 192 per patient per month within 1 year following their initial diagnosis for DLBCL and FL, respectively. The medical costs were nearly twice as much as the drug costs for DLBCL patients. Both DLBCL and FL patients receiving rituximab had higher pharmacy costs but lower medical costs (p < 0.001). During the first year following initial diagnosis, the resource utilization (per patient per month) of DLBCL patients included 0.21 inpatient admissions, 0.26 radiation therapy, 2.63 outpatient or office visits, 0.18 emergency room visits, 0.06 intensive care unit admissions and 0.10 stem cell transplantation. FL patients occupied less health resources than DLBCL patients.Conclusion: The healthcare costs and health resources utilized were considerable in non-Hodgkin's lymphoma, especially DLBCL patients.